Computational Methods in Determination of Pharmacophore Models of 5-HT1A 5-HT2A and 5-HT7 Receptors - Bielenica, Anna; E. Koziol, Anna; Struga, Marta (Mini Reviews in Medicinal Chemistry, 2013)
The present paper discusses models of 5-HT1A and 5-HT2A receptors, developed by conformational analysis and 3D-QSAR methods. Hypotheses concerning the ligand-5-HT7 receptor interaction were complemented by models constructed on the basis of the receptor's structure. Various pharmacophore concepts are supported by structures of exemplary ligands and groups of compounds, derived from chain polycyclic arylpiperazines, used for models generations.
Keywords: pharmacophore model